ANALISIS TINGKAT KEKRITISAN AIR UNTUK KEBERLANGSUNGAN USAHATANI PANGAN MENDUKUNG ADAPTASI TERHADAP PERUBAHAN IKLIM : STUDI KASUS DI PULAU SULAWESI - Woro Estiningtyas; Budi Kartiwa; Dariin Firda (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
Analysis of Water Criticality Level as a Basis for Adaptation of Climate Change for Food Sustainabilty  Farming: A Case Study in Sulawesi Island. Water is a major factor for the growth and sustainability of crop production. The occurrence of climate change has a significant impact on the agricultural sector including water resources. Rainfall as the main water source will change its pattern, intensity and distribution due to climate change so that it greatly affects water availability. This paper aimed to present the level of water criticality and distribution at the district/city level on Sulawesi Island. The level of water criticality was determined based on the ratio between availability and demand for water. Discharge simulations were generated based on the GR2M model. Around 32.1% of district on Sulawesi Island were still at the "critical" level, 50% at the "moderate" level and 17.9% not critical. Districts with a critical status were generally production center areas where water is needed for the sustainability of food farming. Disruption of water availability at this location will result in reduced production. Adaptation efforts need to be undertaken to minimize risks, including through the dissemination and implementation of water-saving technologies in rice cultivation, implementation of irrigation network improvement programs, improvement of critical watersheds, repair and development of irrigation infrastructure especially the development of water harvesting infrastructure (agricultural reservoir, long storage, and trench dams), determining the right time and cropping pattern and the use of adaptive varieties.Keywords: water criticality, water availability, water demands, food farming vulnerability ABSTRAKAir merupakan faktor utama untuk pertumbuhan dan keberlangsungan produksi tanaman. Terjadinya perubahan iklim telah membawa dampak signifikan terhadap sektor pertanian termasuk sumberdaya air. Curah hujan sebagai sumber air utama akan mengalami perubahan pola, intensitas serta distribusinya akibat perubahan iklim sehingga sangat mempengaruhi ketersediaan air. Tujuan penulisan ini adalah menyajikan hasil analisis tingkat kekritisan air dan sebarannya pada level kabupaten/kota di Pulau Sulawesi. Tingkat kekritisan air ditentukan berdasarkan rasio antara ketersediaan dan kebutuhan air. Simulasi debit dibangkitkan berdasarkan model GR2M. Sekitar 32,1% kabupaten/kota di Pulau Sulawesi masih berada pada tingkat “kritis”, 50% pada tingkat “sedang” dan 17,9% belum kritis. Kabupaten/kota dengan status kritis pada umumnya merupakan daerah sentra produksi yang memerlukan air untuk keberlangsungan usahatani pangan. Gangguan ketersediaan air di lokasi ini akan berakibat pada berkurangnya produksi. Upaya adaptasi terkait sumberdaya air perlu dilakukan untuk meminimalkan risiko, antara lain melalui sosialisasi dan implementasi teknologi hemat air dalam budidaya sawah, pelaksanaan program perbaikan jaringan irigasi, perbaikan DAS kritis, perbaikan dan pengembangan infrastruktur irigasi, terutama pengembangan infrastruktur panen air (embung, long storage, dam parit), penentuan waktu dan pola tanam yang tepat serta penggunaan varietas yang adaptif.Kata kunci: kekritisan air, ketersediaan air, kebutuhan air, kerentanan usahatani pangan